Varying the ratio of Lys: Met through enhancing methionine supplementation improved milk secretion ability through regulating the mRNA expression in bovine mammary epithelial cells under heat stress - Fu, Lin; You, Yinjie; Zeng, Yu; Ran, Qifan; Zhou, Yan; Long, Rui; Yang, Heng; Chen, Juncai; Loor, Juan J.; Wang, Gaofu; Zhang, Li; Dong, Xianwen (Frontiers in Veterinary Science, 2024)
Introduction The ratio of lysine (Lys) to methionine (Met) with 3.0: 1 is confirmed as the “ideal” profile for milk protein synthesis, but whether this ratio is suitable for milk protein synthesis under HS needs to be further studied. Methods To evaluate the molecular mechanism by which HS and Lys to Met ratios affect mammary cell functional capacity, an immortalized bovine mammary epithelial cell line (MAC-T) is incubated with 5 doses of Met while maintaining a constant concentration of Lys. The MAC-T cells was treated for 6 h as follow: Lys: Met 3.0: 1 (control 37°C and IPAA 42°C) or treatments under HS (42°C) with different ratios of Lys: Met at 2.0: 1 (LM20), 2.5: 1 (LM25), 3.5: 1 (LM35) and 4.0: 1 (LM40). RNA sequencing was used to assess transcriptome-wide alterations in mRNA abundance. Results The significant difference between control and other groups was observed base on PCA analysis. A total of 2048 differentially expressed genes (DEGs) were identified in the IPAA group relative to the control group. Similarly, 226, 306, 148, 157 DEGs were detected in the LM20, LM25, LM35 and LM40 groups, respectively, relative to the IPAA group. The relative mRNA abundance of HSPA1A was upregulated and anti-apoptotic genes (BCL2L1 and BCL2) was down-regulated in the IPAA group, compared to the control group (p < 0.05). Compared with the IPAA group, the relative mRNA abundance of anti-apoptotic genes and casein genes (CSN1S2 and CSN2) was up-regulated in the LM25 group (p < 0.05). The DEGs between LM25 and IPAA groups were associated with the negative regulation of transcription RNA polymerase II promoter in response to stress (GO: 0051085, DEGs of BAG3, DNAJB1, HSPA1A) as well as the mTOR signaling pathway (ko04150, DEGs of ATP6V1C2, WNT11, WNT3A, and WNT9A). Several DEGs involved in amino acids metabolism (AFMID, HYKK, NOS3, RIMKLB) and glycolysis/gluconeogenesis (AFMID and MGAT5B) were up-regulated while DEGs involved in lipolysis and beta-oxidation catabolic processes (ALOX12 and ALOX12B) were down-regulated. Conclusion These results suggested that increasing Met supply (Lys: Met at 2.5: 1) may help mammary gland cells resist HS-induced cell damage, while possibly maintaining lactation capacity through regulation of gene expression.